Effect of structured discharge teaching after hysterectomy - Nalini Devi, Kshetrimayum; Sheoran, Poonam; Sarin, Jyoti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hysterectomy is the most common major surgical procedure underwent by women. And there is no proper discharge planning for women underwent hysterectomy. The aim of the study was to assess and compare the self-care ability score of women underwent hysterectomy after implementation of structured discharge teaching in experimental and comparison group. Methods: The study was quantitative research approach using non-equivalent control group, post-test only design with 60 women underwent hysterectomy selected by purposive sampling technique from gynae ward of Maharishi Markandeshwar Institute of Medical Science & Research Hospital, Mullana. The post test data was collected by interview technique as 1st follow up visit of operation. Results: The mean score of self-care ability in experimental group (103.63 ± 4.327) was higher than mean score of comparison group (71.67 ± 4.737). The computed ‘t’ value was found to be statistically significant at 0.05 level of significant except personal hygiene and exercise. There was significant association of self-care ability score with days of postoperative stay which was found significant at 0.05 level of significant indicating that self-care ability score was dependent on days of postoperative stay >12 days. Conclusions: The findings revealed that the structured discharge teaching on self-care ability was effective on prevention of complication after hysterectomy. Therefore, it is recommended to develop a proper discharge planning protocol regarding self-care after hysterectomy for prevention of complication.